2017
DOI: 10.1002/bdd.2112
|View full text |Cite
|
Sign up to set email alerts
|

Renal vectorial transport of berberine mediated by organic cation transporter 2 (OCT2) and multidrug and toxin extrusion proteins 1 (MATE1) in rats

Abstract: Berberine, a well-known plant alkaloid derived from Rhizoma coptidis, has potential applications as a therapeutic drug for diabetic nephropathy. However, the transporter-mediated renal transport of berberine remains largely unclear. This study aimed to investigate the renal transport mechanism of berberine using transfected cells, kidney slices and animal experiments. In Madin-Darby canine kidney (MDCK) cells stably expressing rat OCT2 (MDCK-rOCT2) and kidney slices, saturable and non-saturable uptake of berbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Moreover, pyrimethamine as a MATE 1 suppressor, led to a decrease in the urinary excretion of berberine (Shi et al, 2018).…”
Section: Excretionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, pyrimethamine as a MATE 1 suppressor, led to a decrease in the urinary excretion of berberine (Shi et al, 2018).…”
Section: Excretionmentioning
confidence: 98%
“…Co‐administration of an OCT2 inhibitor (corticosterone) and berberine in rats, resulted in a decrease in the urinary excretion of berberine. Moreover, pyrimethamine as a MATE 1 suppressor, led to a decrease in the urinary excretion of berberine (Shi et al, 2018).…”
Section: Pharmacokinetic Parametersmentioning
confidence: 99%
“…Similarly, OCT2 mediated BBR renal carrier transport. As an OCT2 inhibitor, corticosterone could inhibit BBR efflux at high concentrations [ 118 , 119 ]. Experimental studies have found that, in the absence of inhibitors (e.g., pyrimethamine and corticosterone), BBR could induce pharmacokinetic interactions by combining with other drugs to inhibit OCT- and MATE1-mediated transport [ 120 , 121 ].…”
Section: The Interaction Between Drugsmentioning
confidence: 99%
“…In this way, it was difficult for Ber to rapidly and passively diffuse through cell membranes (Berberine 1991;Zhang et al 2014). However, as a substrate of organic cation transporter 1 (OCT1, SLC22A1 gene) and organic cation transporter 2 (OCT2, SLC22A2 gene), Ber could be taken up into cells at a relatively fast rate (Nies et al 2008;Shi et al 2018). OCT2 is also expressed in the central nervous system.…”
Section: Cellular Uptake and Subcellular Location Of Bermentioning
confidence: 99%